2021
DOI: 10.1186/s12885-021-08837-x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and prediagnostic health care contacts in children with cancer in Denmark: a nationwide register study

Abstract: Background While underlying mechanisms and pathways of social inequalities in cancer survival have been extensively examined in adults, this is less so for children with cancer. Hypothesized mechanisms include prediagnostic utilization of and navigation through the health care system, which may differ by socioeconomic resources of the families. In this nationwide register-based study we investigated the association between measures of family socioeconomic position in relation to prediagnostic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…Prematurity and birth asphyxia are leading causes of child mortality worldwide, and the influence of socioeconomic factors is well‐known, also in high‐income settings as the Nordic countries, and perhaps especially in Denmark. 15 , 16 Thus, the present results followed the general pattern to some extent.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Prematurity and birth asphyxia are leading causes of child mortality worldwide, and the influence of socioeconomic factors is well‐known, also in high‐income settings as the Nordic countries, and perhaps especially in Denmark. 15 , 16 Thus, the present results followed the general pattern to some extent.…”
Section: Discussionsupporting
confidence: 82%
“…Second, Pedersen et al found that among Danish children with cancer, families with socioeconomic disadvantage, non‐Western origin or depression were more frequent users of pre‐diagnostic healthcare services. 16 This indicated that even in the high‐income setting of Denmark, some families struggle to navigate in the healthcare system even when their child is severely ill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were some statistically significant findings, there were no clear patterns and inclusion of these clinical characteristics in the regression models of early mortality did not appreciably change effect estimates. Two previous studies assessed the association between socioeconomic status or parental education, and white blood cell count among children with leukaemia, and observed no associations, 26,27 although children of single parents were more likely to have a higher white blood cell count. 27 The first symptoms of childhood cancer are often few and unspecific, 28 and an increased utilization of primary care has been documented already several months before the diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Studies show that lower-class parents need significantly more consultations than parents of higher socioeconomic status to obtain a cancer diagnosis. At the same time, children of parents who are unemployed or have low education levels generally receive lower doses of chemotherapy (Pedersen, Erdmann, et al, 2021). Because discrimination is highly taboo and very often happens unconsciously, we know extremely little about why and how these inequalities occur.…”
Section: Unequal Access To Universal Health Carementioning
confidence: 99%